Broadway, Skagway, Alaska, ca. 1899. - La Roche, Frank (1893)
Caption on image: ""Broadway, Skagway"" Also shows tracks of the White Pass and Yukon Railroad running down Broadway. Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number